CUSUM Learning Curve Analysis in Medical Imaging Education: A Review of Competency Assessment Research Progress - Wen, Dan (Ilmu Inovasi Nusantara, 2025)
The rapid advancement of medical imaging technology has introduced significant challenges in the field of medical imaging education, particularly concerning the allocation of teaching resources, the evaluation of students' skill acquisition, and the need for innovative teaching methodologies. While simulation-based training and objective assessment tools have become increasingly common in medical education, there remains a notable lack of effective quantitative approaches to monitor and evaluate the development of students' diagnostic imaging competencies, especially in areas such as medical imaging report writing. This study aims to systematically review current developments in medical imaging education and the reform of instructional practices, with a specific emphasis on the application of the Cumulative Sum Control Chart (CUSUM) learning curve analysis in clinical skills training. Using a literature review methodology, this paper synthesizes relevant studies from both domestic and international sources to assess the role and potential of CUSUM in enhancing medical imaging education. The findings reveal that the use of CUSUM in this field is still limited, despite its strong potential as an objective, continuous method to assess student progress and identify learning plateaus or improvements. Furthermore, CUSUM analysis can inform the development of evidence-based, data-driven curricula that respond more effectively to learners' needs. Based on these insights, this study recommends the integration of CUSUM learning curve analysis into the framework of medical imaging education as a strategic approach to improve instructional quality, ensure objective skill assessment, and support the continuous improvement of educational practices in the digital age